THE DEPICTION OF THE MAIN CHARACTER'S RESISTANCE AGAINST GENDER ROLES IN BRAVE - I Nyoman Darma Satya; Ni Wayan Sukarini; Ni Luh Sutjiati Beratha (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
The representation of gender roles in media such as movies plays an important role in shaping the social and cultural values of behavioral expectations of individuals within society. While many studies have examined the depiction of traditional gender roles in movies, a few of them focuses on how the main character resists these roles and challenge patriarchal traditions. This study analyzes Brave with a focus on the main character’s resistance against gender roles through the perspective of radical feminism. The purpose of this study is to describe how the main character challenges patriarchal expectations and traditional gender norms in the narrative, and asserts her independence within a patriarchal context. The data were collected the movie scenes and dialogues through documentation and note-taking techniques. The data were analyzed using narrative analysis in qualitative method by applying feminism theory proposed by Tong (2009), which focusing on radical feminism as a lens. The findings identify three forms of resistance by the main character: the resistance against arranged marriage, the resistance against femininity roles, and the resistance of personal autonomy. These forms of resistance reflect radical feminist principles by directly opposing patriarchal structures and affirming women’s right to self-determination. The study concludes that Brave not only illustrates gender roles but also provides a critical narrative of resistance, demonstrating the potential of animated movies to question and reconstruct social and cultural understandings of gender.Keywords: gender, gender roles, radical feminism, resistance